Domino effect: what is it? how it connects to economic activities - Laidin, Jamilah; Ismail, Nor Azira; Ismail, Shahiszan (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2024)
The domino effect is the phenomenon whereby one incident starts a series of connected events. The term "domino effect" originates from the image of dominoes falling in sequence after the first one is tipped. According to Cambridge Dictionary (n.d.), the Domino Effect is “the situation in which something, usually something bad, happens, causing other similar events to happen”. In terms of economics, it explains how a single change in one area of the economy can set off a chain reaction of changes in other sectors as well. This idea is commonly seen in economic activity, when modifications in one market or sector can have a ripple effect on others, resulting in broad economic effects (Kose & Claessens, 2013). Understanding the domino effect in economics can help policymakers, investors, and businesses make informed decisions. For example, the domino effect can be used to explain how an increase in diesel prices can impact other sectors of the economy by triggering a chain reaction of related events. When discussing the impact of rising diesel prices on economic activity, it's essential to recognize the cascading effects across various sectors. Diesel fuel is a crucial input for many industries, especially those dependent on transportation and logistics. As the price of diesel increases, the cost of transporting goods rises, leading to higher prices for consumers and reduced profit margins for businesses. This escalation can slow down economic growth, particularly in sectors such as agriculture, manufacturing, and retail, where transportation costs represent a significant portion of operating expenses. The following examples illustrate how increased diesel prices can affect economic activities across different industries.